Communicating Monetary Policy Intentions: The Case of Norges Bank - Amund Holmsen; Jan F. Qvigstad; Øistein Røisland; Kristin Solberg-Johansen (Norges Bank, 2008)
Monetary policy works mainly through private agents' expectations. How precisely future policy intentions are communicated has, according to theory, implications for the outcome of monetary policy. Norges Bank has gone further than most other central banks in communicating its policy intentions. The Bank publishes its own interest rate forecast, along with forecasts of inflation, the output gap, and other key variables. Moreover, Norges Bank aims to be precise about how the policy intentions are formed. The Bank currently uses optimal policy in a timeless perspective as the normative benchmark when assessing the policy intentions. Given the reaction pattern based on the timeless perspective, the Bank identifies and explains the factors that bring about a change in the interest rate forecast from one Monetary Policy Report to the next. The main arguments for publishing the interest rate forecast are discussed and validated against three years of experience with such forecasts. In this paper, we find evidence of reduced volatility in market interest rates on the days with interest rate decisions, which suggests that communicating policy intentions more precisely improves the market participants' understanding of the central bank's reaction pattern.
hdl:11250/2497765
Keywords: E52; E58; 330; transparency; optimal monetary policy; interest rate forecasts